(untitled) (Research, Society and Development, 2020)
Aim: The aim of the present article is to report a case of a large volume periapical granuloma’s surgical treatment in the jaw. Methodology: An observational and descriptive study was realized with the purpose of reporting scientific considerations on the topic. Case Report: A 7 years old child, male, patient went to Hospital da Face’s clinic in Pernambuco, presenting edema in the jaw. At the extraoral examination it was possible to notice a salience in the jaw’s left region and at the intraoral examination the deciduous tooth 75 was presenting extension carious lesion, color alteration and no vitality. After radiographic examination, a surgical approach was chosen to remove the lesion and associated teeth. The collected tissue was sent for histopathological analysis. Discussion: To diagnose the lesion, the radiographic examination is relevant, but limited, because it depends on the clinical experience to do the interpretation. Therefore, the histopathological analysis is essential to define the type of the present odontogenic lesion and to avoid diagnostic errors. Conclusion: the radiological and histopathological correlation is extremely important to determine periapical lesions. The treatment success depends on the aggressive organisms’ control and decrease and the treatment options must be as many conservative as possible in children.